PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PENDEKATAN THINK PAIR SQUARE UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VII1 SMP NEGERI 3 PEKANBARU - Saputri, Rani Eka; ', Sakur; ', Armis (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research aims to improve the learning process and improve the student’s mathematics learning outcomes through the implementation of Cooperative Learning with Think Pair Square Approach. The type of research is the Classroom Action Research with two cycles. The research was conducted in student of grade VII1 Junior High School 3 Pekanbaru on the second semester in the 2015/2016 academic year with the subject of as many as 40 students. The research instrument are consists of learning devices and instrument data collectors. Learning device used in this research are consists of the Syllabus, Lesson plan and Student work sheet. The instrument data to collect used in this research is consists of the observation sheet and math achievement test. Technique of data analysis is analysis of narrative descriptive and analysis of statistical descriptive. The action is successful if the number of students who achieve a score of minimum mastery criteria increase in daily tests I and II. The number of students who achieve a score of minimum mastery criteria on basic, daily test I (first cycle) and daily test II (second cycle) are respectively 37.5%, 52.5%, and 77.5%. Based on the result of the research show that, the learning process has improved and the student’s mathematics learning outcomes have improved after applying the Cooperative Learning with Think Pair Square Approach. The Cooperative Learning with Think Pair Square Approach can be used as an alternative in learning, because it can improve the learning process and improve the student learning outcomes.Key Words: Cooperative Learning, Think Pair Square Approach, learning process, student learning outcomes